Faktor-Faktor yang Mempengaruhi Pemilihan Profesi Akuntansi oleh Mahasiswa Akuntansi - Laela Putri Lestari (Jurnal Bingkai Ekonomi (JBE), 2020)
The research aims to test factors influencing students in accounting majors in the election career as an accountant. Samples were used as many as 119 students of 2015 to 2018 and were still active in 2018 with sampling techniques in the form of convenience sampling. Data retrieval techniques use questionnaires directly shared and analyzed using discriminant analysis techniques. The results of the study showed professional training variables, social value and job market considerations affecting career selection as an accountant. While the variable financial awards, professional recognition, work environment and personality have no effect in the career selection as an accountant. The most widely chosen profession is the profession of an internal accountant or company.